Characterization of a Thermostable DNA Glycosylase Specific for U/G and T/G Mismatches from the Hyperthermophilic Archaeon Pyrobaculum aerophilum - Yang, Hanjing (American Society for Microbiology, 2000)
U/G and T/G mismatches commonly occur due to spontaneous deamination of cytosine and 5-methylcytosine in double-stranded DNA. This mutagenic effect is particularly strong for extreme thermophiles, since the spontaneous deamination reaction is much enhanced at high temperature. Previously, a U/G and T/G mismatch-specific glycosylase (Mth-MIG) was found on a cryptic plasmid of the archaeon Methanobacterium thermoautotrophicum, a thermophile with an optimal growth temperature of 65°C. We report characterization of a putative DNA glycosylase from the hyperthermophilic archaeon Pyrobaculum aerophilum, whose optimal growth temperature is 100°C. The open reading frame was first identified through a genome sequencing project in our laboratory. The predicted product of 230 amino acids shares significant sequence homology to [4Fe-4S]-containing Nth/MutY DNA glycosylases. The histidine-tagged recombinant protein was expressed in Escherichia coli and purified. It is thermostable and displays DNA glycosylase activities specific to U/G and T/G mismatches with an uncoupled AP lyase activity. It also processes U/7,8-dihydro-oxoguanine and T/7,8-dihydro-oxoguanine mismatches. We designate it Pa-MIG. Using sequence comparisons among complete bacterial and archaeal genomes, we have uncovered a putative MIG protein from another hyperthermophilic archaeon, Aeropyrum pernix. The unique conserved amino acid motifs of MIG proteins are proposed to distinguish MIG proteins from the closely related Nth/MutY DNA glycosylases.